Eco-friendly synthesis of chitosan and its medical application: from chitin extraction to nanoparticle preparation - Riyona Desvy Pratiwi; Sjaikhurrizal El Muttaqien; Nunik Gustini; Najla Salsabila Difa; Gita Syahputra; A'liyatur Rosyidah (International Association of Physical Chemists (IAPC), 2023)
Background and Purpose: Chitosan, a chitin deacetylation product, has been applied in nanoparticle or nano-chitosan for medical applications. However, the chitin extraction from crustacean shells and other natural resources, chitin deacetylation, and crosslinking of the chitosan forming the nano-chitosan mostly involve hazardous chemical and physical processes. The risks of these processes to human health and the environment attract the attention of scientists to develop safer and greener techniques. This review aims to describe the progress of harmless chitosan synthesis. Experimental Approach: All strongly related publications to each section, which were found on scientific search engines (Google Scholar, Scopus, and Pubmed), were studied, selected, and then used as references in writing this review. No limitation for the publication year was applied. The publications were searched from April 2022 - June 2023. Key Results: Nano-chitosan could be synthesized in harmless techniques, including the preparation of the chitosan raw materials and crosslinking the chitosan polymer. Enzymatic processes in shell deproteination in the chitin extraction and deacetylation are preferable to reduce the negative effects of conventional chemical-physical processes. Mild alkalines and deep eutectic solvents also provide similar benefits. In the nano-chitosan synthesis, naturally derived compounds (carrageenan, genipin, and valinin) show potency as safer crosslinkers, besides tripolyphosphate, the most common safe crosslinker. Conclusion: A list of eco-friendly and safer processes in the synthesis of nano-chitosan has been reported in recent years. These findings are suggested for the nano-chitosan synthesis on an industrial scale in the near future.